Genetic screening of newborns in Malaysia: an ethico-legal prognosis - Zawawi, Majdah; Abdul Ghani Azmi, Ida Madieha (Oxford University Press, 2014)
Genetic screening of newborns is not a cure in itself, but it is an important tool for physician to diagnose a genetic disease or disorder. It also provides hope for parents of children with these rare diseases for treatment or at least some advice as to how to help these children grow in a more comfortable environment. This article argues that any jurisdiction wishing to introduce a specific genetic screening programme which makes it compulsory for parents of newborn children to submit their children for genetic testing must address the issue of informed consent of the parents, the type of tests that would be carried out and the treatment of the genetic information that has been obtained. Malaysia is used as an example of how these factors might be reflected in the law.